Embracing multiculturalism: Exploring cultural values among students in the global era - Simatupang, Ernawati; Jusmin, Jusmin; Pramita, Roni Andri Andri; Lestari, Lestari; Willies, Aldilla Yulia; Zaghloul, Taha Romadhan (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
This research was motivated by the UNIMUDA Sorong, one of the multicultural campuses in Papua. This research aimed to measure the level of application and understanding of students at the Department of Pancasila and Citizenship Education, Universitas Pendidikan Muhammadiyah (hence: UNIMUDA) Sorong, in strengthening the existence of multiculturalism values in the academic environment. This research was conducted using a qualitative approach with descriptive methods. The subjects and objects of this research were conducted in the Department of Pancasila and Citizenship Education. The results of this study indicated that the value of multiculturalism had been integrated into the department's curriculum. Besides, students from various ethnic, racial, and religious backgrounds could apply the value of multiculturalism to the Papuan environment. Then, students believed that citizenship within the scope of multiculturalism played the most important role in advancing the diversity of Indonesians, so diversity is not a source of conflict but rather for mutual tolerance and mutual respect in building the foundation of Indonesia's ethnic diversity.